2006
DOI: 10.1111/j.1572-0241.2006.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Host Gastric Sialyl-Lewis X and H. pylori SabA Enhances H. pylori Density in Patients Lacking Gastric Lewis B Antigen

Abstract: In Taiwan, H. pylori isolates are 100% BabA-positive, but only 31% of them express SabA. The interaction between gastric sialyl-Le(x) and SabA of H. pylori determines the colonization density of patients expressing gastric Le(b) weakly or not at all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 14 publications
1
97
2
3
Order By: Relevance
“…The minimal structure required for SabA adhesin binding was shown to be NeuAcα2-3Gal (42,43). Accordingly, it has been demonstrated that SabA interaction with the host gastric sialyl-Le x antigen enhances H. pylori colonization in patients with weak or no Le b expression (44).…”
Section: Helicobacter Pylori Adhesion During Persistent Infectionmentioning
confidence: 99%
“…The minimal structure required for SabA adhesin binding was shown to be NeuAcα2-3Gal (42,43). Accordingly, it has been demonstrated that SabA interaction with the host gastric sialyl-Le x antigen enhances H. pylori colonization in patients with weak or no Le b expression (44).…”
Section: Helicobacter Pylori Adhesion During Persistent Infectionmentioning
confidence: 99%
“…Boiled aliquots of bacterial lysates were subjected to sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis, using a minigel apparatus (Bio-Rad), and blotted onto nitrocellulose membranes at 1 mA/cm 2 by use of a semidry blotting system (Biotec Fischer). The filters were blocked with 3% bovine serum albumin in Tris-buffered saline (TBS; 50 mM Tris-HCl, pH 7.5, 150 mM NaCl) and incubated with AK214 (AlpA) (36), AK262 (AlpB) (31), AK275 (BabC), AK276 (BabB), AK277 (BabA) (all described in reference 33), AK278 (SabA) (40), AK281 (HP0227) (this study), AK282 (OipA) (26), or AK257 (CagA) (34) antiserum for at least 4 hours. Either alkaline phosphatase-coupled protein A was used to visualize the antibody bound by decomposition of nitroblue tetrazolium or the blots were developed using horseradish peroxidase-coupled anti-rabbit immunoglobulin G and a Western Lightning detection system (Perkin-Elmer Life Sciences, Boston, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Adhesins with known ligands include SabA, BabA, and HpaA. SabA, a sialic acidbinding adhesin, functions as a hemagglutinin and has been associated with higher colonization density in humans (2,51). BabA binds the Lewis b blood group antigen (4).…”
mentioning
confidence: 99%